A GPS positioning approach exploiting GSM velocity estimates - Peschke, Sven; Bevermeier, Maik; Haeb-Umbach, Reinhold (6th Workshop on Positioning Navigation and Communication (WPNC 2009))
A combination of GPS (global positioning system) and INS (inertial navigation system) is known to provide high precision and highly robust vehicle localization. Notably during times when the GPS signal has a poor quality, e.g. due to the lack of a sufficiently large number of visible satellites, the INS, which may consist of a gyroscope and an odometer, will lead to improved positioning accuracy. In this paper we show how velocity information obtained from GSM (global system for mobile communications) signalling, rather than from a tachometer, can be used together with a gyroscope sensor to support localization in the presence of temporarily unavailable GPS data. We propose a sensor fusion system architecture and present simulation results that show the effectiveness of this approach.
Keywords: cellular radio; distance measurement; global positioning system; Global Positioning System; global system for mobile communications; GPS positioning approach; GSM velocity; gyroscopes; gyroscope sensor; inertial navigation; inertial navigation system; odometer; sensor fusion system architecture; sensors